2018
DOI: 10.7324/rjc.2018.1111726
|View full text |Cite
|
Sign up to set email alerts
|

"Mercury Uptake and Translocation by Indigenous Plants "

Abstract: Contaminated soil can be remediated by various methods. Phytoremediation is an on-site remediation approach that employs plants to remove inorganic pollutants and immiscible soil contents. The remediation potentials of four native plant species namely Tridax procumbens, Ruellia tuberosa, Dodonaea viscosa and Azadirachta indica from Hg-contaminated soils were studied in pot culture experiment. Mercury (Hg) content in plant roots and shoots were analyzed at 20, 40 and 60 th days of the study period. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is widely reported that a higher amount of Hg is retained in the roots than in the shoots of many plants (Cho and Park, 2000;Ericksen and Gustin, 2004;Wang et al, 2015;Ahammad et al, 2018;Sobrino-Plata et al, 2021). Having found in this study that Hg was also accumulated mainly in the Arabidopsis roots in the presence of exogenous Cys (Figure 2B), we were interested to investigate the difference between the roots and shoots in terms of their regulation of the heavy metal chelator transcripts.…”
Section: Discussionmentioning
confidence: 70%
“…It is widely reported that a higher amount of Hg is retained in the roots than in the shoots of many plants (Cho and Park, 2000;Ericksen and Gustin, 2004;Wang et al, 2015;Ahammad et al, 2018;Sobrino-Plata et al, 2021). Having found in this study that Hg was also accumulated mainly in the Arabidopsis roots in the presence of exogenous Cys (Figure 2B), we were interested to investigate the difference between the roots and shoots in terms of their regulation of the heavy metal chelator transcripts.…”
Section: Discussionmentioning
confidence: 70%
“…Mercury is not easily degraded in the environment and thus is considered a mobile contaminant that affects the ecosystem [ 52 ]. Even in small quantities, Hg is hazardous to plants, causing stunted growth and other concerns [ 53 ]. It is released into the environment through anthropogenic activities and via natural sources such as volcanoes and is then spread through the air, soil, and water [ 54 ].…”
Section: Uptake Translocation and Toxicity Of Non-essential Heavy Met...mentioning
confidence: 99%
“…Ren et al [ 56 ] experimentally showed that together with As, Hg severely affected rice seedlings. The toxic effect of Hg on plant systems varies and includes growth retardation, decreased chlorophyll content, protein denaturation, chlorosis, production of ROS, and DNA damage [ 53 , 57 ].…”
Section: Uptake Translocation and Toxicity Of Non-essential Heavy Met...mentioning
confidence: 99%
“…Hg does not have any beneficial effects on organisms and is thus regarded as the "main threat" since it is very harmful to both plants and animals; pollutes the air, water and soil; and is toxic [167]. Mercury has toxic effects on plants, even at low concentrations, and leads to growth retardation [168] and many other adverse effects [105].…”
Section: Toxic Effects On Plantsmentioning
confidence: 99%